Assessment of family planning practices of women of reproductive age group in rural area of Jammu region - Dewan, Deepika; Nazir, Heena; Kakkar, Tania (International Journal Of Community Medicine And Public Health, 2019)
Background: Despite more than fifty years of implementation of National Family Planning and Welfare programme, unmet need for family Planning is still high which poses a big challenge for family planning programme. The aim is to reach all women whose reproductive behaviour requires one or the other forms of contraception but for various factors are not practicing them. Methods: A cross-sectional descriptive study was carried out amongst women of reproductive age group in the field practice area of Rural Health Training Centre of Dept. of Community Medicine of a Government Medical College, Jammu during the period of January to June 2018. Ethical clearance was obtained from the Institutional Ethics committee prior to the start of the study. Total of 541 eligible couples attending the family welfare section were interviewed by the trained staff using the pre-tested questionnaire. The information about various family planning methods adopted by couple was elicited. Data was analysed by using appropriate test whenever necessary. Results: A total of 541 eligible couples were interviewed. Maximum couples were in the age group of 30-34 years. 300 (55.4%) couples were using one or the other method of family planning. Condoms were most commonly used method by 148 (49.3%) couples followed by oral contraceptive pills (30.6%). Among permanent methods of family planning, tubectomy was adopted by 10 (3.3%) and vasectomy only by 4 (1.3%) couples. No one was practising any miscellaneous method of contraception. The percentage of family planning methods used by Hindus was maximum (65%). Difference was also observed in the context of socio-economic status. Conclusions: Nearly half of eligible couples were not practising any method of contraception. There is need to increase motivation among eligible couples to increase adoption of permanent methods of contraception especially vasectomy.